2017
DOI: 10.15381/rivep.v28i3.13362
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de la Alimentación con Pulpa de Café (Coffea arabica) en los Índices Productivos de Cuyes (Cavia porcellus L) Raza Perú

Abstract: RESUMENEl objetivo del estudio fue determinar el efecto de la alimentación con harina de pulpa de café (Coffea arabica) en los índices productivos de cuyes (Cavia porcellus L), raza Perú, durante la etapa de recría y engorde. Se trabajó con 35 cuyes hembras desde los 28 hasta los 91 días de edad, alimentados con dietas a base de alfalfa y concentrado (1:1). Los cuyes fueron distribuidos al azar en cinco tratamientos con inclusiones en el concentrado de 0, 5, 15, 25 y 35% de harina de pulpa de café. La adición … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 4 publications
0
9
0
6
Order By: Relevance
“…Dietary fibre is another component of coffee pulp that can be used to promote a healthy diet. Previous studies reported that dried coffee pulp contains 351.7 g/kg of fibre (Donkoh et al, 1988), and coffee pulp powder from Amazonas Peru has a fibre concentration of 19.29%; these values are similar to or higher than the fibre content of yellow maize and quinoa, two high-consumption cereals of the world (Yoplac et al, 2017).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 79%
See 3 more Smart Citations
“…Dietary fibre is another component of coffee pulp that can be used to promote a healthy diet. Previous studies reported that dried coffee pulp contains 351.7 g/kg of fibre (Donkoh et al, 1988), and coffee pulp powder from Amazonas Peru has a fibre concentration of 19.29%; these values are similar to or higher than the fibre content of yellow maize and quinoa, two high-consumption cereals of the world (Yoplac et al, 2017).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 79%
“…The higher the protein level of the ration the greater the protection against negative effects of coffee pulp on animal yield (Gómez-Brenes et al, 1985). This diet was also evaluated for commercial guine pig (Cavia porcellus L) production: 25% coffee pulp powder was found to increase casing performance (Yoplac et al, 2017).…”
Section: Uses As Food Tablementioning
confidence: 99%
See 2 more Smart Citations
“…Tabla 1. Residuos obtenidos durante el benecio de 1 kg de café Fuente: Rodríguez y Zambrano (2010) Existe una necesidad -mayor en tiempos de crisis-de reducir los costos de alimentación de las explotaciones donde el uso de recursos locales podría ser una alternativa (Flórez-Delgado & Rosales-Asensio, 2018), en especial de aquellas que causan un impacto negativo al medioambiente por su inadecuada disposición, como es el caso de la pulpa de café (Yoplac et al, 2017). La conservación mediante la técnica del ensilaje es una opción segura y económica (Mayorga, 2005) de emplear este residuo en la alimentación animal (Pinto et al, 2014), el cual está compuesto de carbohidratos (21 % a 32 %), proteína (7,5 % a 15 %) y grasa (2 % a 7 %) (Esquivel & Jiménez, 2012).…”
Section: Introductionunclassified